Engineering of PVA/PVP Hydrogels for Agricultural Applications - Eyal Malka; Shlomo Margel (Gels, 2023)
Hydrogels have gained significant popularity in agricultural applications in terms of minimizing waste and mitigating the negative environmental impact of agrochemicals. This review specifically examines the utilization of environmentally friendly, shapable hydrogels composed of polyvinyl alcohol (PVA) and polyvinylpyrrolidone (PVP) in various casings for crop protection against different pests, fertilizing, and watering. To activate their effectiveness, PVA/PVP hydrogels were loaded with both hydrophilic and hydrophobic environmentally friendly pesticides, namely hydrogen peroxide (HP), the essential oil thymol, and urea as a fertilizer, either separately or in combination. This review covers various physical and chemical approaches used for loading, shaping, and controlling the release profiles of pesticides and fertilizers. Additionally, it explores the evaluation of the chemical composition, structure, classification, rheology, and morphology of the hydrogels as well as their impact on the thermal stability of the encapsulated pesticides and fertilizer, followed by biological tests. These hydrogels significantly contribute to the stabilization and controlled release of essential nutrients and biocides for plants, while maintaining excellent biocidal and fertilizing properties as well as sustainability characteristics. By shedding light on the latest insights into the concepts, applications, and results of these hydrogels, this review demonstrates their immense potential for widespread future use in agriculture.